Reception of the Western World in Russian and Persian Literature of the 19th–20th Centuries: Woe from Wit by A. S. Griboyedov and Jafar Khan Came from Europe by H. Moghadam - Janolah Karimi-Motahhar; Soroush Salimi; Marzieh Yahyapour (Два века русской классики, 2025)
In order to analyze the peculiarities of Western European influence on the culture of Russia and Iran in the 19th–20th centuries, the article compares the comedies Woe from Wit by A. S. Griboyedov and Jafar Khan Came from Europe by Hasan Moghadam. The pathos of exalting the original Russian culture permeates Griboyedov’s comedy. Thanks to the intercultural ties between Iran and Russia, the Iranian literary community was influenced by Russian drama. In addition, at the beginning of the 20th century, when the play Jafar Khan Came from Europe was written, the social situation in Iran resembled that of the early 19th century in Russia. Like Griboyedov, Moghadam welcomed the socio-political liberation in his country and objected to its cultural Westernization. The article reveals contactological and typological similarities between the works of Russian and Iranian playwrights of the 19th and 20th centuries.